The WIRED Trial - Wii Sports™ as a virtual Reality Exercise Experience to improve Depression in healthcare workers during the COVID-19 Pandemic: A Multicenter, Prospective, Randomized, Controlled, Superiority Phase II Trial. (Principles and Practice of Clinical Research, 2021)
Background: Due to the coronavirus pandemic, the number of hospitalized individuals increased exponentially. The sudden increase in workload, the social isolation, and the fear of COVID-19 contributed to a remarkable increase of depression cases (from 20.9% to 43.2%) among healthcare workers. Although many treatments are available for depression, including pharmacotherapy, exercise, and virtual reality, response varies widely, from complete recovery to non-responders and relapsing cases. In this sense, Wii Sports™ may serve as an alternative to improve response to standard first-line therapy, since it provides an interactive environment, physical activity and incorporates playfulness. Objective: Evaluate the effect of Wii Sports™ in treating mild and moderate cases of major depressive disorder in healthcare professionals who developed depression during the COVID-19 pandemic.Methods: The WIRED trial is a phase II, multicenter, randomized, active-controlled, single-blinded, superiority trial with two parallel groups. The intervention group will be composed of Wii Sports™ in addition to a first-line antidepressant, while the control group will be composed of Wii™ games that do not involve physical activity in addition to a first-line antidepressant. The primary outcome is to detect a group mean difference in the 17-item Hamilton Depression Rating Scale (HAM-D17) at week twelve, while secondary outcomes include participant adherence and comparison of HAM-D17 scores at different time points.Conclusion: To our knowledge, there is no previous literature published that targets the same population, tests the same intervention, and evaluates the same outcomes, highlighting the possible impact of the study on the psychological and psychiatric fields, regardless of its results.Keywords: Coronavirus, COVID-19, depression, Major Depression Disorder, Wii Sports™, virtual reality, exercise.